Comparative Outcomes of Primary Vitrectomy Versus Tap and Inject for Endophthalmitis Following Phacoemulsification Cataract Surgery. (3rd April 2022) - Crosby, Niall J.; Westcott, Mark; Michael, Eugene; Cunningham, William J.; Welch, Sarah; Polkinghorne, Philip J.
ABSTRACT: Purpose: To compare functional and anatomical outcomes, rates of culture positivity and number of procedures in eyes with endophthalmitis following phacoemulsification surgery, treated with either primary vitrectomy and intravitreal antibiotics or vitreous tap and antibiotic injection (T&I). Methods: Patients developing endophthalmitis after phacoemulsification surgery between 2007 and 2016 were identified, and outcomes were compared between the two treatment groups. Results: 19 patients underwent a primary vitrectomy and 22 underwent a T&I. There was a significant improvement in visual acuity after T&I (p=.003) and primary vitrectomy (p=.00005). The median improvement in visual acuity was significantly greater for the primary vitrectomy group than the T&I group (p=.024). 64% of eyes were culture positive with the initial T&I, and 63% with primary vitrectomy (p=1.00). Two eyes initially culture negative with a T&I, and three eyes that were culture positive with a T&I were subsequently culture positive with a vitrectomy 24-72 hours later. 68% of patients who underwent a T&I required an additional procedure, compared to 26% of the vitrectomy group (p=.01). The T&I group underwent a mean of 2.3 procedures each, and the primary vitrectomy group underwent 1.5 (p=.03). Conclusions: Eyes with endophthalmitis treated with a primary vitrectomy demonstrated greater visual improvement and needed fewer procedures than those initially treated with a T&I. Viable bacteria were only seen in subsequent procedures in the T&I group, indicating that primary vitrectomy was superior at sterilizing the eye.